Measuring the effectiveness of marketing expenditure - Ambler, Tim (Henry Stewart Talks, 2010)
The use of metrics, Review of the Australian Marketing Institute webware for dashboard metrics selection and design, Layout design, Should the Australian system be adopted elsewhere?, Marketing performance, Brand valuation, Silver metrics, DCF techniques in performance measurement and planning, The bottom line, Benefits from well designed market dashboards